Antibiotics in interventional radiology. Issue 3 (March 2015) - Sutcliffe, J.A.; Briggs, J.H.; Little, M.W.; McCarthy, E.; Wigham, A.; Bratby, M.; Tapping, C.R.; Anthony, S.; Patel, R.; Phillips-Hughes, J.; Boardman, P.; Uberoi, R.
<x xml:space="preserve">Abstract</x> The range and number of interventional procedures is rapidly increasing each year. A major complication associated with many procedures is infection, which can result in serious adverse outcomes for the patient. Consequently, antibiotics are amongst the most common pharmaceuticals used by the interventionist, particularly for non-vascular procedures, yet almost no randomized controlled trial data exist to inform our decision when formulating appropriate antibiotic prophylaxis regimens. The purpose of this review is to provide an update on the utilization of antibiotics for common interventional radiology procedures, focusing on timing and duration of antibiotic prophylaxis.